LET’S VACATION IN JAPAN! A STUDY OF INDONESIAN IMAGES OF JAPAN THROUGH TOURISM - Kaneko, Masanori (PEOPLE: International Journal of Social Sciences, 2019)
The number of outbound Indonesian travelers is rapidly increasing, especially in travel to long-haul destinations. For these travelers, Japan is considered a favorite and trendy destination. This is due not only to Indonesia’s own push factors like its stable economy, but also structural changes in Japan. In 2011, the total number of foreign travelers to Japan dropped sharply after the horrible news of an earthquake and tsunami in the Tohoku area and the serious atomic power plant accident that followed in Fukushima. After these catastrophic disasters, the Japanese government intensely promoted inbound tourism to recover its damaged economy; this included waving visa requirements for short-term stays for visitors from countries like Indonesia, the Philippines, and Vietnam. The Japan Tourism Agency and the Japan National Tourism Organization, as well as travel agents and aviation companies, are important actors in promoting inbound tourism to Japan. As a result, compared with 2011, the number of Indonesian travelers in 2017 increased by approximately 5.7 times. Along with travelers’ personal decisions, the roles of government bodies and private companies are very important for understanding the recent tourism dynamics. Travelers do not always need a correct and holistic understanding of the culture, but something “authentic,” “unique,” or “exotic” for them to share with friends and family. This paper also shows how Indonesian travelers to Japan reflectively reconstruct and disseminate stereotypical images of the country through various channels including video sharing services like YouTube, or social network services like Instagram and Facebook. Although biased and limited, the accumulation and dissemination of Indonesians’ personal experiences are now changing their images of Japan from monotonous to empirical and concrete.